Biological iron-based composite material as well as preparation method and application thereof
By preparing bioferro-based composite materials, the synergistic effect of denitrifying bacteria and FeNPs and combined with the adsorption performance of resin materials, the problems of high energy consumption, low stability and low degradation efficiency of existing kitchen waste degradation technologies are solved, and efficient and environmentally friendly kitchen waste degradation effects are achieved.
Patent Information
- Application Number
- CN202411806702.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
Smart Images

Figure CN119608734A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of kitchen waste degradation, and in particular to a biological iron-based composite material and a preparation method and application thereof. Background Art
[0002] Food waste is an important component of urban solid waste, and its generation is increasing year by year, which has brought great pressure to the environment. Although traditional treatment methods, such as landfill and incineration, can temporarily solve the garbage problem, they often lead to waste of land resources, emission of greenhouse gases such as carbon dioxide and methane, and release of harmful substances during the treatment process. Especially in landfills, the decomposition of food waste will produce a large amount of greenhouse gases, increasing the risk of global warming. Therefore, it is particularly important to explore efficient and environmentally friendly food waste treatment technologies.
[0003] In recent years, microbial technology has been widely used in waste treatment and resource recovery. Microorganisms have unique advantages in decomposing organic matter and can convert complex organic matter into simple inorganic matter. At the same time, microorganisms can also react with metal ions to generate iron nanoparticles (FeNPs), which are an emerging environmentally friendly material widely used in water treatment and soil remediation.
[0004] FeNPs have a large specific surface area and good catalytic properties, and can degrade organic pollutants and inhibit the generation of harmful gases during anaerobic decomposition. However, the traditional FeNPs preparation method is complicated and requires harsh conditions, high energy consumption and the use of a large number of chemical reagents. In addition, the prepared materials have high biochemical activity and poor stability during use, resulting in low degradation efficiency, which limits its application in food waste treatment. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a bio-iron-based composite material and a preparation method and application thereof.
[0007] (II) Technical solution
[0008] The first object of the present invention is to provide a method for preparing a bio-iron-based composite material, which is simple, low-cost, energy-saving and environmentally friendly, and suitable for industrial production.
[0009] The second object of the present invention is to provide a bio-iron-based composite material, which has a large specific surface area, high activity, strong stability, and can effectively promote the degradation of organic matter in kitchen waste.
[0010] The third object of the present invention is to provide an application of a bio-iron-based composite material, which, when used for the degradation of kitchen waste, can efficiently decompose organic matter in the waste, increase the degradation rate, and inhibit the generation of harmful gases.
[0011] In order to achieve the above object, the preparation method of the bio-iron-based composite material of the present invention comprises:
[0012] S1. Cultivate denitrifying bacteria and perform iron acclimatization;
[0013] S2, adding an iron source to a culture medium containing domesticated denitrifying bacteria to obtain a denitrifying bacteria-FeNPs composite material;
[0014] S3, adding the resin material into the culture medium containing the denitrifying bacteria-FeNPs composite material to carry out an adsorption reaction, so as to obtain the denitrifying bacteria-FeNPs@resin composite material.
[0015] The present invention firstly acclimates denitrifying bacteria to iron elements, and then uses the biological reduction ability of bacteria to synthesize FeNPs to form a denitrifying bacteria-FeNPs composite material, wherein the hydrogen generated by FeNPs during the corrosion process can be used as an electron donor for anaerobic bacteria, reduce the redox level, provide a more suitable growth environment for bacteria, and increase the biodegradation rate, thereby rapidly reducing the concentration of pollutants to weaken the inhibitory effect on indigenous microorganisms, thereby promoting the growth of microorganisms, while the denitrifying bacteria can protect the FeNPs from being oxidized by the environment, and the two promote each other; finally, the denitrifying bacteria-FeNPs composite material is adsorbed by a resin material to obtain a denitrifying bacteria-FeNPs@resin composite material, and the resin adsorption performance is used to adsorb microorganisms in the environment, and phosphorus sources, nitrogen sources and organic matter necessary for microorganisms are effectively enriched, thereby improving the stability and biological activity of the denitrifying bacteria-FeNPs.
[0016] Optionally, the culture medium for culturing denitrifying bacteria comprises water, protein, yeast extract, a sodium source, a nitrogen source, a phosphorus source, a zinc source, a copper source, a cobalt source and a manganese source; wherein,
[0017] The protein content is 3-7 g / L;
[0018] The content of the yeast extract is 1 to 3 g / L;
[0019] The content of the sodium source is 8-12 g / L;
[0020] The content of the nitrogen source is 3-7 g / L;
[0021] The content of the phosphorus source is 1 to 3 g / L;
[0022] The content of the zinc source is 0.01-0.05 g / L;
[0023] The content of the copper source is 0.01-0.05 g / L;
[0024] The content of the cobalt source is 0.01 to 0.05 g / L;
[0025] The content of the manganese source is 0.01-0.05 g / L.
[0026] Optionally, the culturing of denitrifying bacteria and iron acclimation comprises:
[0027] After the concentration of the denitrifying bacteria reaches 1-8×108 cfu / mL, 0-1 mL, 1-2 mL, 2-3 mL, 3-4 mL and 4-5 mL of an iron source with a concentration of 25-40 mM are added to the culture medium at set intervals to perform iron acclimation;
[0028] The pH value of the culture medium is 7-7.5, and the temperature is 25-37° C. The shaking speed is controlled to be 200-230 rpm, and the culture time is 4-6 hours.
[0029] Optionally, the iron source in step S2 is a ferric chloride solution, and the molar addition amount of iron in the iron source is 135 to 162 mmol.
[0030] Optionally, the resin material in step S3 is D201 resin;
[0031] The conditions of the adsorption reaction include: a temperature of 20 to 25° C. and a system pH of 7 to 7.5.
[0032] Optionally, the resin material is subjected to impurity removal and activation treatment before use.
[0033] Optionally, after step S3, the following steps are further included:
[0034] The denitrifying bacteria-FeNPs@resin composite material is sequentially washed with water, immersed in glutaraldehyde solution and washed with PBS buffer solution.
[0035] The bio-iron-based composite material of the present invention is obtained by the preparation method as described above.
[0036] The bio-iron-based composite material of the present invention is used for the degradation treatment of kitchen waste, can efficiently decompose organic matter in the kitchen waste, and greatly reduce the generation of harmful gases during the decomposition process.
[0037] Optionally, the conditions for the degradation treatment include: a system pH value of 7 to 7.5 and a temperature of 30 to 37°C.
[0038] (III) Beneficial effects
[0039] The preparation method of the bio-iron-based composite material in the present invention is simple, low-cost, energy-saving and environmentally friendly, and suitable for industrial production. The prepared bio-iron-based composite material has both biological and chemical activities, strong stability, and can effectively promote the degradation of kitchen waste. Among them, the hydrogen generated by FeNPs during the corrosion process can be used as an electron donor for anaerobic bacteria, reduce the redox level, and provide a more suitable environment for bacteria to grow. At the same time, it promotes microbial diversification and increases the biodegradation rate, thereby rapidly reducing the concentration of pollutants to weaken the inhibitory effect on indigenous microorganisms, thereby promoting microbial growth, and denitrifying bacteria can protect FeNPs from being oxidized by the environment. The two promote each other and work synergistically to improve the activity of the material; the composite resin has excellent adsorption properties, can adsorb microorganisms in the environment, and effectively enrich the phosphorus source, nitrogen source and organic matter necessary for microorganisms, which is beneficial to improve the stability and biological activity of denitrifying bacteria-FeNPs. Through the synergistic effect of the three, the composite material has excellent biochemical activity and significantly improves the degradation rate of kitchen waste;
[0040] When the bio-iron-based composite material of the present invention is used for the degradation of kitchen waste, it can efficiently decompose organic matter in the kitchen waste and inhibit the generation of harmful gases. Microorganisms decompose organic matter under the action of FeNPs, and FeNPs can catalyze the degradation of organic matter and promote degradation. The two promote each other, significantly improve the degradation rate and inhibit the generation of harmful gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The present invention is a flow chart of the preparation method of the bio-iron-based composite material. DETAILED DESCRIPTION
[0042] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with the accompanying drawings through specific embodiments. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0043] Embodiment 1:
[0044] Step 1: Material preparation;
[0045] Kitchen waste: Steamed bread, rice, cabbage, and pork were prepared in a mass ratio of 5:5:4:4. Specifically, each group was crushed and added to a 3L plastic measuring cylinder according to the above ratio. Each plastic measuring cylinder was filled with 1000g of simulated kitchen waste, and then 500mL of physiological saline was added.
[0046] Microbial strain: Denitrifying bacteria Pseudomonas aestus nigri PAEI01.
[0047] Iron source: ferric chloride
[0048] Liquid culture medium: 1 L of deionized water, 5 g of peptone, 1 g of yeast extract, 10 g of sodium chloride, 5 g of sodium nitrate (as a nitrogen source), 0.5 g of sodium dihydrogen phosphate, 0.5 g of disodium hydrogen phosphate, 0.01 g of zinc sulfate, 0.01 g of copper sulfate, 0.01 g of cobalt chloride, and 0.01 g of manganese chloride.
[0049] Step 2: Cultivation of denitrifying bacteria and iron acclimation;
[0050] The above liquid culture medium was used as a liquid culture medium (1 L) for preparing denitrifying bacteria, the pH value was adjusted to 7, denitrifying bacteria were added, and the culture was shaken (28° C., 200 rpm). After the culture, the concentration of the denitrifying bacteria was 1×108 cfu / mL. Then, ferric chloride solution (36 mM) was added to the liquid culture medium once every 3 days, and the volume was gradually increased from 0-1, 1-2, 2-3, 3-4, and 4-5 mL to acclimate the denitrifying bacteria and adapt them to the iron element. The liquid culture medium was replaced before each addition of ferric chloride solution.
[0051] Step 3: Synthesis of denitrifying bacteria-FeNPs composite materials;
[0052] After cultivation and domestication, the denitrifying bacteria have adapted to the iron element. 4.5 mL of ferric chloride solution (36 mM) is added to the liquid culture medium of the denitrifying bacteria after the above cultivation and iron domestication. The bacteria use their biological reduction ability to synthesize FeNPs to obtain a culture solution containing denitrifying bacteria-FeNPs.
[0053] Step 4: Preparation of denitrifying bacteria-FeNPs@D201;
[0054] Wash 10 grams of D201 resin with sterile deionized water 2-3 times to remove impurities and residues. Soak the washed D201 resin in sterile PBS buffer and let it stand for 1 hour to keep the solution uniform. Add the treated D201 resin to 100 mL of culture solution containing the above-mentioned denitrifying bacteria-FeNPs and let it stand for 2 hours to allow the denitrifying bacteria-FeNPs to be fully adsorbed on the surface of the D201 resin. After the adsorption is completed, gently wash the resin with deionized water 2-3 times to remove trace amounts of unadsorbed nitrifying bacteria-FeNPs. To ensure the adsorption and cross-linking effect, transfer the D201 resin adsorbed with denitrifying bacteria-FeNPs to a glutaraldehyde solution with a mass concentration of 2.5%, soak it for 2 hours for cross-linking, and promote the stable binding of bacteria and resin. After completion, the bacteria and resin complex was thoroughly washed with sterile PBS buffer (phosphate buffered saline, the most widely used buffer in biochemical research, with main components of Na2HPO4, KH2PO4, NaCl and KCl, generally used as a solvent to dissolve protective reagents) to remove unbound glutaraldehyde and obtain the denitrifying bacteria-FeNPs@D201 composite material.
[0055] Embodiment 2:
[0056] The denitrifying bacteria-FeNPs@D201 composite material was prepared by the method of Example 1, except that after the adsorption reaction of D201 resin added to the culture solution of denitrifying bacteria-FeNPs was completed, the denitrifying bacteria-FeNPs@D201 composite material was directly washed with clean water without being immersed in a glutaraldehyde solution.
[0057] Comparative Example 1:
[0058] The denitrifying bacteria-FeNPs composite material was prepared by the method of Example 1 without being compounded with a resin material, and a culture solution containing denitrifying bacteria-FeNPs was directly obtained.
[0059] Embodiment 3:
[0060] Prepare 4 portions of the above-mentioned kitchen waste respectively and add them to 4 reactors respectively. Add the denitrifying bacteria-FeNPs@D201 composite material prepared in Example 1 to the first reactor; add the denitrifying bacteria-FeNPs@D201 composite material prepared in Example 2 to the second reactor; add the culture solution containing denitrifying bacteria-FeNPs obtained in Comparative Example 1 to the third reactor; the fourth reactor does not add other substances and serves as a blank control group. Control the pH in all reactors to 7.5 and the temperature to 35°C, and detect the degradation of kitchen waste in each reactor. Among them, Table 1 is the properties of each material; Table 2 is the moisture content during the degradation of kitchen waste; Table 3 is the soluble chemical oxygen demand during the degradation of kitchen waste; Table 4 is the cellulase during the degradation of kitchen waste; Table 5 is the amylase during the degradation of kitchen waste; Table 6 is the waste gas during the degradation of kitchen waste.
[0061] Table 1 Properties of each material
[0062] characteristic D201 FeNPs@D201 <![CDATA[Specific surface area (m 2 / g)]]> 9.16 25.35 Average pore size (nm) 16.12 9.87
[0063] The specific surface area of FeNPs@D201 is significantly higher than that of D201, reaching 25.35 m 2 / g, providing more reaction sites and surface space. During the degradation process, microorganisms such as denitrifying bacteria can attach to the surface of the material and use its large specific surface area to carry out biodegradation reactions.
[0064] The higher specific surface area of FeNPs@D201 also enhances the material's ability to adsorb organic matter, especially for organic matter or small molecular pollutants dissolved in kitchen waste, which can provide better catalytic and degradation conditions. At the same time, the reduction in the average pore size of FeNPs@D201 can make the pore structure denser, so that microorganisms can obtain a more stable growth environment in a smaller pore size, improve the stability of microorganisms, and thus improve the efficiency of biodegradation.
[0065] Table 2 Moisture content during the degradation of kitchen waste
[0066]
[0067] The moisture content not only affects the metabolism of microorganisms, but also determines the aerobic fermentation efficiency of kitchen waste. Except for the water content of the blank control group set in the fourth reactor, which has been decreasing, the moisture content of the remaining groups increased before 24 hours and decreased after 24 hours. The final products of microbial metabolism of organic matter under aerobic conditions are water and carbon dioxide. The inoculation of bacterial agents keeps the number of microorganisms in kitchen waste at a high level, and metabolism produces a large amount of water. Since the microbial content carried by the kitchen waste itself in the blank control experiment is too low, the liquid produced by metabolism is minimal, and the moisture content gradually decreases. Comparative Example 1, Example 1 and Example 2 all contain denitrifying bacteria-FeNPs, with high aerobic fermentation efficiency and high moisture content. Due to the presence of D201 resin that can enrich the flora, Example 1 and Example 2 have a very high microbial content, which can effectively increase the rate of microbial metabolism, thereby increasing the moisture content between 0h and 24h.
[0068] Table 3 Dissolved chemical oxygen demand during the degradation of kitchen waste
[0069]
[0070] Soluble chemical oxygen demand is an important indicator to characterize the hydrolysis situation. Microorganisms hydrolyze kitchen waste, decompose macromolecules into small molecules, and increase the content of soluble organic matter. The soluble chemical oxygen demand of comparative example 1, example 1 and example 2 are all higher than that of the blank control group, and the soluble chemical oxygen demand of example 1 and example 2 is much higher than that of comparative example 1, indicating that the denitrifying bacteria-FeNPs@D201 composite material can significantly promote the degradation of kitchen waste.
[0071] Table 4 Cellulase in the process of kitchen waste degradation
[0072]
[0073] Table 5 Amylase in the process of kitchen waste degradation
[0074]
[0075] Hydrolases are important detection indicators in the process of kitchen waste degradation. At different fermentation stages, the changes in substrate hydrolase activity can reveal the mineralization and decomposition process of organic matter in kitchen waste from the perspective of microbial structure. In the comparison of cellulase activity and amylase activity, it can be seen from Tables 4 and 5 that the two enzyme activities of Comparative Example 1, Example 1 and Example 2 are higher than those of the blank control group, the two enzyme activities of Example 1 and Example 2 are higher than those of Comparative Example 1, and the two enzyme activities of Example 1 are higher than those of Example 2. Therefore, it is shown that the FeNPs wrapped by denitrifying bacteria and the denitrifying bacteria-FeNPs@D201 composite material can ensure the activity of biological enzymes, which is beneficial to the degradation of kitchen waste, and the resin material can further improve the activity of denitrifying bacteria-FeNPs.
[0076] Table 6 Waste gas during the degradation of kitchen waste
[0077]
[0078] The composition of kitchen waste is complex, and it will produce foul-smelling gases (mainly sulfides) during the degradation process, which seriously pollutes the environment and affects production. Compared with the blank control group and comparative example 1, the denitrifying bacteria-FeNPs@D201 composite materials of Example 1 and Example 2 can significantly reduce the release of hydrogen sulfide, carbon disulfide and methyl mercaptan during the degradation of kitchen waste.
[0079] It can be proved that the denitrifying bacteria-FeNPs@D201 composite material of the present invention can effectively promote the degradation of organic matter in the kitchen waste, while reducing the generation of harmful gases, especially sulfides. Specifically, the prepared biological iron-based composite material has both biological and chemical activities, strong stability, and can efficiently promote the degradation of kitchen waste, wherein the hydrogen generated by FeNPs during the corrosion process can be used as an electron donor for anaerobic bacteria, reduce the redox level, provide a more suitable environment for bacteria to grow, and promote microbial diversification, increase the biodegradation rate, and then quickly reduce the concentration of pollutants to reduce the inhibitory effect on indigenous microorganisms, thereby promoting microbial growth, and denitrifying bacteria can protect FeNPs from being oxidized by the environment, and the two promote each other and synergistically improve the activity of the material; the composite resin has excellent adsorption performance, can adsorb microorganisms in the environment, and effectively enrich the phosphorus source, nitrogen source and organic matter necessary for microorganisms, which is conducive to improving the stability and biological activity of denitrifying bacteria-FeNPs, and through the synergistic effect of the three, the composite material has excellent biochemical activity and significantly improves the degradation rate of kitchen waste. During the degradation of kitchen waste, the bio-iron-based composite material can efficiently decompose organic matter in the kitchen waste and inhibit the generation of harmful gases. Among them, microorganisms decompose organic matter under the action of FeNPs, and at the same time, FeNPs can catalyze the degradation of organic matter and promote degradation. The two promote each other, significantly increase the degradation rate and inhibit the generation of harmful gases.
[0080] In the description of this specification, the description of the terms "one embodiment", "some embodiments", "embodiment", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0081] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may alter, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a biological iron-based composite material, characterized in that: The preparation method of the biological iron-based composite material comprises: S1. Cultivate denitrifying bacteria and perform iron acclimatization; S2, adding an iron source to a culture medium containing domesticated denitrifying bacteria to obtain a denitrifying bacteria-FeNPs composite material; S3, adding the resin material into the culture medium containing the denitrifying bacteria-FeNPs composite material to carry out an adsorption reaction, so as to obtain the denitrifying bacteria-FeNPs@resin composite material.
2. The method for preparing the bio-iron-based composite material according to claim 1, characterized in that: The culture medium for culturing denitrifying bacteria comprises water, protein, yeast extract, sodium source, nitrogen source, phosphorus source, zinc source, copper source, cobalt source and manganese source; wherein, The protein content is 3-7 g / L; The content of the yeast extract is 1 to 3 g / L; The content of the sodium source is 8-12 g / L; The content of the nitrogen source is 3-7 g / L; The content of the phosphorus source is 1 to 3 g / L; The content of the zinc source is 0.01-0.05 g / L; The content of the copper source is 0.01-0.05 g / L; The content of the cobalt source is 0.01 to 0.05 g / L; The content of the manganese source is 0.01-0.05 g / L.
3. The method for preparing the bio-iron-based composite material according to claim 1 or 2, characterized in that: The culturing of denitrifying bacteria and iron acclimation comprises: After the concentration of the denitrifying bacteria reaches 1-8×108 cfu / mL, 0-1 mL, 1-2 mL, 2-3 mL, 3-4 mL and 4-5 mL of an iron source with a concentration of 25-40 mM are added to the culture medium at set intervals to perform iron acclimation; The pH value of the culture medium is 7-7.5, and the temperature is 25-37° C. The shaking speed is controlled to be 200-230 rpm, and the culture time is 4-6 hours.
4. The method for preparing the bio-iron-based composite material according to claim 1, characterized in that: The iron source in step S2 is a ferric chloride solution, and the molar amount of iron added in the iron source is 135 to 162 mmol.
5. The method for preparing the bio-iron-based composite material according to claim 1, characterized in that: The resin material in step S3 is D201 resin; The conditions of the adsorption reaction include: a temperature of 20 to 25° C. and a system pH of 7 to 7.
5.
6. The method for preparing the bio-iron-based composite material according to claim 1 or 5, characterized in that: The resin material is subjected to impurity removal and activation treatment before use.
7. The method for preparing the bio-iron-based composite material according to claim 1, characterized in that: After step S3, the following steps are also included: The denitrifying bacteria-FeNPs@resin composite material is sequentially washed with water, immersed in glutaraldehyde solution and washed with PBS buffer solution.
8. A bio-iron-based composite material, characterized in that: The bio-iron-based composite material is obtained by the preparation method according to any one of claims 1 to 7.
9. An application of the bio-iron-based composite material as claimed in claim 8, characterized in that: Used for the degradation of kitchen waste.
10. The use of the bio-iron-based composite material according to claim 9, characterized in that: The conditions of the degradation treatment include: the system pH value is 7-7.5, and the temperature is 30-37°C.
Citation Information
Patent Citations
Method for purifying and absorbing spraying granulation flue gas by utilizing resin complex
CN110496526A
Preparation method of denitrifying bacterium nano-iron composite material for underground water denitrification
CN110589987A
Preparation method and application of modified cyanobacteria biochar loaded nano zero-valent iron material
CN114105290A
Microorganism immobilization support
JP2002233885A
Method for functionalising surface of magnetic nanoparticles
RU2543631C2